QUALITY OF LIFE ASSESSMENT IN CARDIAC TRANSPLANT RECIPIENTS - A. O. Shevchenko; T. A. Khalilulin; B. L. Mironkov; R. Sh. Saitgareev; V. M. Zakharevich; A. Ya. Kormer; I. I. Muminov; S. V. Gautier (Вестник трансплантологии и искусственных органов)
Background. Quality of life (QoL) is an important criterion for the treatment effi cacy that provides an important data regarding patient’s personal estimation of social adaptation and ability to perform daily duties.Methods. The study was aimed to evaluate QoL in cardiac transplant recipients. We have enrolled 42 stage D heart failure patients aged 29–61 (mean 39,23 ± 12,31 y/o), 38 males and 4 females, survived cardiac transplant surgery between Jan 2008 and Jan 2013. QoL was evaluated using the SF-36 survey prior to the heart surgery and during the follow-up period up to the 5 years.Results. Pre-operative assessment revealed low QoL indices of physical activity as well as general health status. Follow-up showed dramatic improvement in all QoL measures during 1 year after the surgery which was consistent through the whole observation period. There was an increase in physical functioning index by 2,8 times (p < 0,01), physical status dependent role functioning by 14 times (р < 0,0001), emotional status dependent role functioning by 3 times (р = 0,02), social functioning by 4,8 times (p = 0,002), pain threshold by 3 times (p = 0,02), psychic health by 3,6 times (p = 0,001), life activity by 2,6 times(p = 0,003), and total health by 1,6 times (p = 0,03). Physical activity was restored in 90% of patients during the fi rst year.Conclusion. The study shows signifi cant improvement in all QoL variables after heart transplantation in stage D heart failure patients. Main indices of physical, psychical, and social activities rise at the fi rst year and remain high during the 5-year period. These data support heart transplantation as a radical and effective method of terminal heart failure treatment.